Tren Fintech Terhadap Crowdfunding dan Blockchain di Era Revolusi Industri 4.0 - Respati, Adnasohn Aqilla; Seraf, Yudea Maruli; Gracy, Clony Christy; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
Through research In this article, readers can understand FinTech and its innovations, such as understanding Crowdfunding and Blockchain. Talking about innovation in FinTech in a nutshell is an important part of finance, including asset aggregation, market making, risk management, and information clearing. Then this article also discusses the scope of crowdfunding and blockchain. The discussion regarding crowdfunding points to financial technology in the form of fintech innovation which does not eliminate the need for financial intermediaries. The aim of this research is to understand the topic of Financial Technology and the development of FinTech and show readers that modern studies of FinTech are fragmented with a controlled and structured theoretical basis. Through this research, the author uses normative research, which means that problems will be raised, discussed and explained focusing on the application of rules or norms in positive law in Indonesia.